BJOG Editor's Choice. (December 2016) - Marsh, Michael
Abstract : Deputy Editor‐in‐Chief, Mr. Michael Marsh, discusses his top articles from this issue in an audio podcast available at:https://soundcloud.com/bjog/december-editors-choice-2016 .